Quality of Information: The role of internal controls and materiality - Leif Christensen (Copenhagen Business School (CBS), 2016)
Accounting and auditing is closely related to the quality of data. Two important elements supporting the quality of information are internal controls and materiality. Inspired by Simons (1994), these elements can be considered “basic building blocks”. Internal controls are perhaps the most important element, as they ensure that information used for management purposes has the required quality (Kinney, 2000). This information can be used as a basis for preparing the external financial reporting (COSO, 2013) and as a prerequisite for establishing information-based management control systems (MCS) (Simons, 1994). When regarding management controls as a package, internal controls are part of the administrative controls and often formalised in policies and procedures (Malmi and Brown, 2008). The level of controls should be guided by the need for reliable information. These considerations are linked to another “basic building block”, namely the concept of materiality. The basic meaning of materiality is “that there is no need to be concerned with what is not important or with what does not matter” (Bernstein, 1967). Gaining an understanding of these concepts is important in order to answer the question “when is enough – enough?” The information should be both reliable and relevant, but there is also the cost to consider, since companies spend considerable resources on the design, implementation and operation of administrative controls and financial reporting (Carney, 2006). It is also important to understand these concepts when performing an audit of the internal controls embedded in the company systems and processes (Kinney et al., 2013), as well as when preparing an annual report. The overall objective of this thesis is to add to the understanding of the role of internal controls and materiality. The three articles included aim at meeting this objective by analysing selected areas within accounting and auditing.
hdl:10398/9353
Keywords: 650